2016
DOI: 10.1016/j.actamat.2016.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Twin boundary activated α → ω phase transformation in titanium under shock compression

Abstract: The role of grain boundary structures on the shock response of hexagonal-closepacked (hcp) metals is little understood. We use molecular dynamics simulations to investigate deformation mechanisms in shock compressed Ti bicrystals with three types of grain boundary (GB) microstructure. Our results show the shock response of phase Ti polycrystals are influenced by the GB characteristics, i.e., elastic shock wave induced inelastic deformation occurs on both sides of the {1012} coherent twin boundaries (CTBs) but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…It should be mentioned that RDF plots have been used to demonstrate structural phase transition in materials 38 , 39 . Thus, RDF plots are also considered to analyze in this work.…”
Section: Resultsmentioning
confidence: 99%
“…It should be mentioned that RDF plots have been used to demonstrate structural phase transition in materials 38 , 39 . Thus, RDF plots are also considered to analyze in this work.…”
Section: Resultsmentioning
confidence: 99%
“…However, the roles of CTBs played in the phase transition of iron are still not clear. Most recently, researches on CTB and phase transition in Ti has brought out some new insights into deformation mechanisms, as well as its interactions with phase transition, under shock or uniaxial compressions [31][32][33][34][35]. Zong et.…”
Section: Introductionmentioning
confidence: 99%
“…al. [31] also studied the roles of three types of GBs played in the phase transition of Ti under shock compressions, and found that CTB can facilitate nucleation of the phase transition because the CTB is more similar to metastable state in transition path from α to ω phase, and thus helps overcome energy barrier of the phase transition. Despite of these progresses, interactions between CTB and the direction or reverse phase transition at lattice level are still a mystery in BCC metals.…”
Section: Introductionmentioning
confidence: 99%
“…[5,8,10,15,17]. Three distinctive characteristics of shock loading and HPT conditions are worth noting: (i) both impose significant shear to the material and as such, naturally activate large amounts of twinning in addition to dislocation glide [18,19]; (ii) postmortem microscopy analysis of shock-loaded Zr shows that the retained αgrains are lath-shaped, which resembles closely the conventional morphology of deformation twins [7,20]; (iii) atomistic calculations show that under shock loading, coherent twin boundaries in Ti act as favorable nucleation sites for the α-to-ω phase transformation compared to incoherent twin boundaries and random grain boundaries [21]. Taken together, we speculate that under shock loading and HPT conditions, αgrains first twin and then the ω-phase nucleates at or in the vicinity of twin boundaries.…”
Section: Introductionmentioning
confidence: 99%